2015
DOI: 10.1021/jacs.5b04636
|View full text |Cite
|
Sign up to set email alerts
|

Ultra-High-Response, Multiply Twisted Electro-optic Chromophores: Influence of π-System Elongation and Interplanar Torsion on Hyperpolarizability

Abstract: The systematic synthesis, structural, optical spectroscopic, and second-order nonlinear optical (NLO) characterization of a series of donor-acceptor poly-arylene chromophores which have heretofore unachieved π-extension and substantial twisting from planarity, are reported: specifically, two-ring 2TTMC, dicyano(4-(3,5-dimethyl-1-(2-propylheptyl)pyridin-1-ium-4-yl)-3-methylphenyl)methanide; three-ring 3TTMC, dicyano(4'-(3,5-dimethyl-1-(2-propylheptyl)pyridin-1-ium-4-yl)-2,2',3',5',6'-pentamethyl[1,1'-biphenyl]-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
69
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(78 citation statements)
references
References 152 publications
1
69
0
Order By: Relevance
“…In such (D‐A‐π‐A‐D) molecules TPA cross‐sections σ 2 = 890 GM at 790 nm (1.57 eV) for the dibutylamino‐terminated and σ 2 = 730 GM at 825 nm (1.50 eV) for the corresponding biphenylamino‐terminated α‐CN‐2PV were obtained . To gain nevertheless access to the TPA properties of both compounds and to relate them to the findings of Pond et al, we performed quantum chemical calculations that were shown earlier to reliably predict the trends among 2 substituted pheneylene vinylene chromophores . The calculated TPA cross‐sections and the associated excited state energies are given in Table .…”
Section: Resultsmentioning
confidence: 97%
“…In such (D‐A‐π‐A‐D) molecules TPA cross‐sections σ 2 = 890 GM at 790 nm (1.57 eV) for the dibutylamino‐terminated and σ 2 = 730 GM at 825 nm (1.50 eV) for the corresponding biphenylamino‐terminated α‐CN‐2PV were obtained . To gain nevertheless access to the TPA properties of both compounds and to relate them to the findings of Pond et al, we performed quantum chemical calculations that were shown earlier to reliably predict the trends among 2 substituted pheneylene vinylene chromophores . The calculated TPA cross‐sections and the associated excited state energies are given in Table .…”
Section: Resultsmentioning
confidence: 97%
“…So, researchers have paid more and more attentions to organic EO materials in the past decades. And a large amount of novel organic EO materials with excellent EO activity has been emerged [6][7][8][9][10]. Else, the development of novel EO devices including organic EO modulator, optical switch, terahertz detectors and so on is also very fast.…”
Section: Introductionmentioning
confidence: 99%
“…This resulted in better film-forming ability, higher electro-optics coefficients and better long-term stability. Quantum chemical simulations of the second order polymers have been reported in the past two decades, it is very difficult to find organic second order nonlinear optical materials that have both large electro optic coefficients and long-term stability [13][14][15][16][17][18]. Due to the large EO coefficients of about 42-78 pm/V (all the EO parameters are given at wavelength 1.3 µm) at low chromophore loading density (10 wt%), chromophore CLDs have been widely studied, but their thermal decomposition temperature is very low (~180 °C) [53].…”
Section: Introductionmentioning
confidence: 99%